Electro-pulse-enhanced cancer therapy - Persson, Bertil R. R. (Cambridge Scholars Publisher, 2020)
This book provides knowledge about how cancerous tumour treatment using electrical pulses can increase efficiency and reduce the side effects of established tumour treatment methods. The combination of electrical pulses and chemotherapy has so far been successfully performed on more than 3000 patients, and using such pulses in conjunction with radiation therapy is a tempting challenge. The text provides a coherent presentation of the knowledge needed for successful treatment using electrical pulses in clinical practice. This method does not require access to high-tech resources and therefore i